Formulation Of Revenue Enhancement Strategy For PDAM Tirta Bhagasasi - Tirtajaya, Mas Deden; Putra, Purnama (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2025)
Article 33 of the 1945 Constitution states that the earth, water and natural resources that are stored are owned by the state and used for the welfare of the people. Given the large role and function of clean water in Indonesia, that is why the Government has built several clean water treatment institutions managed by Regional Owned Enterprises, namely Regional Drinking Water Companies known as PDAMs. The purpose of this study was to identify the internal and external factors of PDAM Tirta Bhagasasi Bekasi. The research method used in this research is to use a combination of quantitative and qualitative methods in parallel applied in the SWOT and QSPM matrix analysis. This study uses the SWOT analysis method (Strengths, Weaknesses, Opportunities, Threats). In answering the research questions, the authors use EFAS and IFAS analysis by conducting interviews guided by questions in the questionnaire as well as an in-depth review of the PDAM Tirta Bhagasasi document. Based on the research that has been carried out, it is obtained that PDAM Tirta Bhagasasi as a regional-owned company generally has a healthy performance based on the IFAS and EFAS analysis, there are 12 Internal Factors as a Strength component, 10 Weakness Components and 6 External Factors Opportunity component, 6 Threat factor components at PDAM Tirta Bhagasasi.